C/EBPβ mediates anti-proliferative effects of 1, 25(OH)2D on differentiated thyroid carcinoma cells. Issue 6 (9th May 2022) - Xu, Feng; Ling, Yali; Yuan, Jingjing; Zeng, Qin; Li, Lusha; Dai, Dexing; Xia, Xuedi; Sun, Ruoman; Zhang, Ran; Xie, Zhongjian
Abstract : Differentiated thyroid carcinoma (DTC) is the most common endocrine malignancy and highly expresses the receptor for 1, 25-dihydroxyvitamin D (1, 25(OH)2 D). However, it is unclear whether 1, 25(OH)2 D regulates DTC proliferation and differentiation. Here, we found that 1, 25(OH)2 D3 inhibited proliferation but not differentiation of the DTC cells. Notably, CYP27B1 was elevated in DTC cells and 25-hydroxyvitamin D3 (25(OH)D3 ) reduced DTC cell proliferation. Knockdown of VDR did not affect the anti-proliferative effects of 1, 25(OH)2 D3 . However, knockdown of CCAAT enhancer-binding protein β (C/EBPβ) abolished 1, 25(OH)2 D3 -suppressed DTC cell proliferation. In addition, 1, 25(OH)2 D3 induced phosphorylation and translocation of C/EBPβ to the nucleus from the cytoplasm. However, inhibition of p38 mitogen-activated protein kinases (MAPK) abrogated 1, 25(OH)2 D3 -induced phosphorylation and nuclear translocation of C/EBPβ as well as 1, 25(OH)2 D3 -suppressed DTC cell proliferation. Knockdown of C/EBPβ reduced the expression of Notch3 . Knockdown of Notch3 blocked 1, 25(OH)2 D3 -suppressed DTC cell proliferation. In the DTC cell-derived xenograft SCID mouse, knockdown of C/EBPβ markedly increased tumor growth and proliferation and decreased apoptosis. In DTC patients, C/EBPβ was predominantly located in the cytoplasm of DTC cells in the tumor tissue when compared with adjacent non-cancerous tissue in which C/EBPβ is located in the nucleus. In conclusion, C/EBPβ stimulated Notch3 signaling via the p38 MAPK-dependent pathway mediates the inhibitory effect of 1, 25(OH)2 D on DTC cell proliferation.